2003
DOI: 10.1111/j.1525-1438.2003.13603.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (Fact/GOG-Ntx) questionnaire for patients receiving systemic chemotherapy

Abstract: The purpose of this study was to validate the Functional Assessment of Cancer Therapy/Gynecologic Oncology Group-Neurotoxicity (FACT/GOG-Ntx) questionnaire. The FACT/GOG-Ntx is the FACT-G plus an eleven-item subscale (Ntx subscale) that evaluates symptoms and concerns associated specifically with chemotherapy-induced neuropathy. Two groups of women with ovarian cancer completed the FACT/GOG-Ntx: one group with known neurotoxicities and one group of chemotherapy-naive women newly diagnosed with ovarian cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
248
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(252 citation statements)
references
References 8 publications
1
248
0
3
Order By: Relevance
“…One key issue is that the PRO measures should be defined upfront and during trial development, with patients involved in their production. PRO measures used for ovarian cancer include generic, tumor-specific, treatment-specific or symptom-specific measures (226,228,229) and involve face-to-face interview schedules (230), quality of life questionnaires (227-229, 231, 232), satisfaction scales and patient preference approaches (233).…”
Section: [H1]quality Of Lifementioning
confidence: 99%
“…One key issue is that the PRO measures should be defined upfront and during trial development, with patients involved in their production. PRO measures used for ovarian cancer include generic, tumor-specific, treatment-specific or symptom-specific measures (226,228,229) and involve face-to-face interview schedules (230), quality of life questionnaires (227-229, 231, 232), satisfaction scales and patient preference approaches (233).…”
Section: [H1]quality Of Lifementioning
confidence: 99%
“…Regular clinical assessment by symptom history taking and subjective assessment of functionality, both at baseline and during therapy with bortezomib, are central to evaluating changes in patient symptoms. A patientreported questionnaire specific for neurotoxicity, such as the Functional Assessment of Cancer Therapy/Gynecology Oncology Group-Neurotoxicity questionnaire, may be very useful in alerting physicians to this problem [25]. With early detection and the use of an algorithm established for dose reduction based on experience in phase II trials (Table 3) [6,23], more patients can be promptly diagnosed and dose reductions implemented.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…QOL: Health-related qol was measured using various domains of the European Organisation for Research on Treatment of Cancer Quality of Life Questionnaire-Core (qlq-C30) 88 in two studies 47,76 . In a subanalysis of the vista trial 24 , Dhawan et al 47 showed that newly diagnosed mm patients treated with bortezomib, melphalan, and prednisone had a higher sustained rate of improvement in health-related qol than did patients treated with melphalan and prednisone (14 of 15 domains).…”
Section: Pfsmentioning
confidence: 99%